Incubation of Fear. Issue 1 (15th July 2013) - Pickens, Charles L.; Golden, Sam A.; Nair, Sunila G.
Abstract: While fear and anxiety can grow over time in anxiety disorders, most efforts to model this phenomenon with fear conditioning in rodents cause fear that remains stable or decreases across weeks or months. Here, we describe several methods to induce conditioned fear that grows over the course of 1 month and is sustained for at least 2 months using an extended fear conditioning approach. These methods include a very reliable standard method that causes multiple fear measures to increase over months, as well as alternative methods. Curr. Protoc. Neurosci . 64:6.27.1‐6.27.11. © 2013 by John Wiley & Sons, Inc.